Perancangan Sistem Informasi Jadwal Kegiatan Pelayanan dan Pendaftaran Ibadah Pada Gereja Pentakosta Indonesia Sidang Tanjung Sari Berbasis Web - Debora Grace Daeli; Ginting, Wasit; Romanus Damanik (LOFIAN: Jurnal Teknologi Informasi dan Komunikasi, 2023)
The Covid-19 pandemic has had a huge negative impact on all areas. The Indonesian Pentecostal Church of the Tanjung Sari Congregation is a place of worship that was affected by Covid-19 causing the church to limit both activities and the number of people who worship at the church. These restrictions make it difficult for the congregation and guests to get information regarding the schedule of service activities and even have difficulty getting seats to worship because of restrictions on the number of people who attend offline worship. So with the Design of an Information System for Service Activity Schedules and Worship Registration at the Indonesian Pentecostal Church, the Tanjung Sari Assembly will help overcome problems related to delivering information to the congregation and guests of the Tanjung Sari Assembly. The method used in making this information system is to use the prototype model, where the flow and stages used include identifying users and developing prototypes. With this system, all congregation members and guests can obtain information regarding the exact schedule of weekly service activities and can register for worship to get seats in offline worship. In this system the congregation and guests only fill in their personal data so that they can access and find out all activities and officers from the church who as admins will always notify all activities that will be held.